Language-in-Education Policy of Kazakhstan: Post-Pandemic Technology Enhances Language Learning - Dinara Tlepbergen; Assel Akzhigitova; Anastassia Zabrodskaja (MDPI AG, 2022)
In the current times of rapid technological progress, the development of quality education and encouragement of educated youth are extremely important. For this reason, a number of state projects and programs were developed in the education system of modern Kazakhstan. This paper is devoted to the problems of multilingual education and emergency remote learning in this country. The primary objectives were to examine the language competence and preferences of undergraduates and to explore the impact of the COVID-19 pandemic on remote language learning. Here, we present the survey and interview results of non-linguistic specialty students regarding their language preferences in various spheres, as well as the difficulties encountered during distance learning.